Propagation of elastic waves in adhesive contacts: experiment and numerical model - Lyashenko, Iakov A.; Filippov, Aleksander E.; Popov, Valentin L. (Frontiers in Mechanical Engineering, 2024)
Entrance and propagation of the pores inside adhesive interface between elastomer and rigid sphere is studied experimentally and simulated numerically. It is shown that mutually interacting events of attachment-detachment of the different segments of elastomer to the indenter lead to the nontrivial patterns of the spatially distributed contact between them, which is additionally influenced by the air penetrating inside the pores.